Dynamics of Infected Active and Uninfected Active Populations Leading to Pandemics by Using a Discrete Model of Two Interacting Pacemakers - Sergey Belyakin; Sergey Shuteev (New Trends in Physical Science Research Vol. 1, 2022)
We generalize the proposed model of two interacting oscillators in the case of a strong difference in their periods (when the pacemaker pulses do not alternate) and propose a General model describing a network of oscillators coupled globally.Our goal is to keep the model as simple as possible, with as few parameters as possible. As a result, we’ll properly characterise the pacemakers in terms of their intrinsic cycle durations and recast them as pulse oscillators. PRC describes the interaction of pacemakers. . In works on lattices of concatenated maps, two main types of coupling are usually considered: nearest neighbor coupling and global coupling.